APLIKASI PENJULAN PRODUK SARANG BURUNG WALET DMI MENGGUNAKAN METODE WATERFALL - Steven Cang; Desi Arisandi; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Ram Swallow Nest DMI is a business engaged in sales. Where the sale of swallow nests at Ram Swallow Nest DMI is assessed from several aspects, namely in terms of shape, quality, weight and price. This sale is carried out manually where the seller and buyer make an agreement in advance for the location before the transaction occurs after the transaction agreement is made and the transaction is recorded manually into the note then must be transferred back manually into the sales ledger. So that sales and processing at Ram Swallow Nest DMI are less efficient and time consuming. Created a web-based sales system on sales and data processing Ram Swallow Nest DMI which aims to facilitate sales and recording transactions, increase efficiency and practical. And this website was also developed using HTML programming, CSS, Laragon database and Laravel framework.